Method for depositing electron transport layer for perovskite solar cell through alcohol-assisted chemical bath and perovskite solar cell
Through the alcohol-assisted chemical bath deposition method, the aggregation problem of SnO2 electron transport layer in perovskite solar cells is solved, the uniformity and transmittance of the layer are improved, and the photoelectric conversion efficiency and stability of perovskite solar cells are improved.
Patent Information
- Application Number
- CN202411351839.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-26
AI Technical Summary
In perovskite solar cells, the SnO2 electron transport layer is prone to agglomeration during chemical bath deposition, resulting in uneven surfaces, reducing electron transport efficiency, and introducing defects, affecting battery efficiency and light utilization.
Using alcohol-assisted chemical bath deposition method, by adding SnCl2·2H2O, urea, thioglycolic acid and concentrated hydrochloric acid to the aqueous isobutanol solution, a chemical bath solution was formed, and the SnO2 electron transport layer was deposited, using the coordination bonds and steric positions of isobutanol The resistance effect slows down the aggregation of SnO2 particles and improves the nucleation density and transmittance.
The uniformity and transmittance of the SnO2 electron transport layer are improved, the photoelectric conversion efficiency, open circuit voltage and short circuit current density of perovskite solar cells are improved, and the solar light utilization rate and cell stability are enhanced.
Smart Images

Figure CN119233732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cells, and in particular to a method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell and a perovskite solar cell. Background Art
[0002] In the high-end equipment manufacturing industry, among the new solar cells, perovskite solar cells (PSCs) have been one of the most promising technologies in recent years and have received extensive attention from academia and industry. The photoelectric conversion efficiency (PCE) has exceeded 26%. In perovskite solar cells, the role of the electron transport layer is to extract electrons and hinder hole transport, which plays a pivotal role. At present, the commonly used electron transport layer is SnO2. SnO2 has high volume electron mobility and high conductivity, a wider band gap (3.6-4.0eV) and high transmittance, and can be processed at low temperature, which can be applied to flexible perovskite solar cells. However, the performance of SnO2 is closely related to its preparation method. The commonly used preparation methods are spin coating, atomic layer deposition and chemical bath deposition. Spin coating is a commonly used preparation method in the laboratory, but it cannot be applied to large-area preparation; although atomic layer deposition can be used for large-area preparation, the equipment is expensive, so chemical bath deposition began to be used in the preparation of SnO2.
[0003] However, during the chemical bath deposition process, SnO2 nanoparticles will inevitably agglomerate, causing their surface to become uneven, reducing the effective contact area and thus reducing the electron transmission efficiency; and the agglomerated SnO2 can introduce more defects at the interface with the perovskite layer. These defects will act as centers for charge recombination, increase non-radiative recombination, reduce the open circuit voltage and short-circuit current density of the battery, and thus reduce the battery efficiency; in addition, SnO2 agglomeration will also affect light scattering and reflection, reducing the amount of light absorbed by the perovskite layer, thereby affecting the photocurrent and overall efficiency of the battery. Summary of the invention
[0004] The present invention provides a method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell and a perovskite solar cell to solve the above problems.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In one aspect, the present invention provides a method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell, comprising the following steps:
[0007] S1: cleaning the conductive glass substrate to obtain a clean conductive glass substrate;
[0008] S2: adding SnCl2·2H2O to an isobutyl alcohol aqueous solution to obtain a first mixed solution, adding urea to the first mixed solution to obtain a second mixed solution, and then mixing thioglycolic acid, concentrated hydrochloric acid, and the second mixed solution to complete the preparation of a chemical bath solution;
[0009] S3: Soak the clean conductive glass substrate in a chemical bath solution and place it in an oven for a deposition reaction. After the reaction is completed, the conductive glass substrate is cleaned and annealed to complete the deposition of the SnO2 electron transport layer on the conductive glass substrate.
[0010] Furthermore, in S2, the volume fraction of the isobutanol aqueous solution is 0-20%.
[0011] Furthermore, in S2, the concentration of urea in the second mixed solution is 12-13 mg / mL.
[0012] Furthermore, in S2, the concentration of SnCl2·2H2O in the first mixed solution is 2-3 mg / mL.
[0013] Furthermore, in S2, the thioglycolic acid, concentrated hydrochloric acid and the mixed solution are mixed in a volume ratio of 1:50:80.
[0014] Further, in S3, the annealing temperature is 100-200° C., and the annealing time is 1-2 h.
[0015] Furthermore, in S3, the temperature of the oven is 70-90°C and the time is 3-5h.
[0016] Furthermore, the conductive glass substrate is a fluorine-doped tin oxide conductive glass substrate.
[0017] Furthermore, in S1, the specific method of cleaning is: ultrasonic cleaning with detergent, deionized water, anhydrous ethanol, and isopropanol for 15-30 minutes each;
[0018] In S3, the specific method of cleaning is: ultrasonically cleaning the substrate with deionized water and isopropyl alcohol in sequence for 5-10 minutes.
[0019] On the other hand, the present invention provides a perovskite solar cell, comprising a conductive glass substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer arranged in a stacked manner, wherein the electron transport layer is an electron transport layer prepared by the method for alcohol-assisted chemical bath deposition of electron transport layer for perovskite solar cells described in the present invention.
[0020] The beneficial effects of the present invention are:
[0021] The present invention discloses a method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell. Compared with a SnO2 electron transport layer deposited from a simple aqueous solution, the SnO2 electron transport layer deposited from the alcohol-assisted chemical bath by the method has better uniformity, reduced agglomeration of nanoparticles, and higher sunlight transmittance, which is beneficial to improving the sunlight utilization rate of the perovskite solar cell, and can also reduce the open circuit voltage and short-circuit current density of the battery, thereby improving the photoelectric conversion efficiency of the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 Surface SEM images of four SnO2 electron transport layers prepared in Examples 1-3 of the present invention and Comparative Examples (Figure (a) is SnO2 deposited by a 5% volume fraction of isobutanol chemical bath; Figure (b) is SnO2 deposited by a 10% volume fraction of isobutanol chemical bath; Figure (c) is SnO2 deposited by a 20% volume fraction of isobutanol chemical bath; Figure (d) is SnO2 deposited by a water solution (not containing isobutanol) chemical bath);
[0024] Figure 2 The UV spectra of four SnO2 electron transport layers prepared in Examples 1-3 of the present invention and the comparative example are shown;
[0025] Figure 3 The current density-voltage curve of the perovskite solar cell prepared by the SnO2 electron transport layer deposited by the isobutanol chemical bath with a volume fraction of 5% in Example 1 of the present invention;
[0026] Figure 4 The current density-voltage curve of the perovskite solar cell prepared by using the SnO2 electron transport layer deposited by a chemical bath with a volume fraction of 10% isobutanol in Example 2 of the present invention;
[0027] Figure 5 The current density-voltage curve of the perovskite solar cell prepared by the SnO2 electron transport layer deposited by the isobutanol chemical bath with a volume fraction of 20% in Example 3 of the present invention;
[0028] Figure 6 The current-voltage curve of the perovskite solar cell prepared by the SnO2 electron transport layer deposited by chemical bath of aqueous solution (without isobutanol) in the comparative example of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The principle involved in the present invention is that the hydroxyl group of isobutanol can form a coordination bond with the tin ions in the deposition solution, and the coordination effect can reduce the reaction activity and slow down the hydrolysis and aggregation rate; and the isobutanol has an isobutyl structure and has a steric hindrance effect, and the steric hindrance can prevent the mutual contact between SnO2 particles and slow down the aggregation rate; at the same time, the isobutanol can be evenly distributed in the solution, providing more active sites for the nucleation of SnO2, thereby increasing the nucleation density, reducing the aggregation of particles, and further improving the transmittance of sunlight, so that the sunlight utilization rate of the perovskite solar cell is improved, and finally the efficiency of the perovskite solar cell is improved.
[0031] Example
[0032] Embodiment 1:
[0033] A method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell comprises the following steps:
[0034] S1: Cleaning of transparent conductive substrate
[0035] The fluorine-doped tin oxide conductive glass substrate (FTO) was ultrasonically cleaned with detergent, deionized water, anhydrous ethanol, and isopropanol for 15 min each;
[0036] S2: Preparation of chemical bath solution
[0037] 5 ml of isobutanol and 45 ml of water are mixed to obtain an isobutanol aqueous solution, wherein the volume fraction of isobutanol is 5%, and then 137.5 mg of SnCl2·2H2O is added to the isobutanol aqueous solution to obtain a first mixed solution, wherein the concentration of SnCl2·2H2O is 2.75 mg / mL; 625 mg of urea is added to the first mixed solution to obtain a second mixed solution, wherein the concentration of urea is 12.5 mg / mL; then 12.5 uL of thioglycolic acid, 625 uL of concentrated hydrochloric acid and 1 ml of the second mixed solution are mixed, and stirred until clarified, thereby completing the preparation of the chemical bath solution;
[0038] S3: Chemical bath deposition of SnO2 electron transport layer
[0039] The cleaned FTO was placed vertically into the chemical bath solution and placed in a 90°C oven for deposition reaction for 3.5 hours. After the reaction, the substrate was ultrasonically cleaned with deionized water and isopropanol for 5 minutes, and then annealed at 170°C for 1 hour to complete the deposition of the SnO2 electron transport layer on the FTO.
[0040] S4: sequentially depositing a perovskite layer, a hole transport layer Spiro-OMeTAD and a vapor-deposited electrode layer on the SnO2 electron transport layer to prepare a perovskite solar cell, the specific method being:
[0041] Deposition of perovskite layer: MABr (8.4 mg), PbBr2 (27.53 mg), MACl (28.86 mg), FAI (245.06 mg), PbI2 (656.94 mg) were dissolved in a solvent of DMSO (125 uL) and DMF (875 uL) to obtain a perovskite precursor solution; 30 uL of the perovskite precursor solution was dropped on a substrate deposited with SnO2, followed by a two-stage spin coating process (rotation speed 1000 rpm, spin coating time 10 s and rotation speed 3000 rpm, spin coating time 30 s) to spin coat the perovskite precursor solution, and 15 s before the end of the second stage of spin coating, 200 uL of anti-solvent chlorobenzene was continuously dropped on the rotating substrate, and then the prepared film was annealed at 120 ° C for 40 min to obtain a perovskite film (perovskite layer);
[0042] Deposition of hole transport layer Spiro-MeOTAD: 72.3 mg Spiro-MeOTAD, 17.5 uL acetonitrile solution of LITFSI (520 mg / mL), 20 uL acetonitrile solution of FK209 (300 mg / mL), and 28.8 uL tetra-tert-butylpyridine were dissolved in 1 mL chlorobenzene to obtain a hole transport layer precursor solution, 15 uL of the hole transport layer precursor solution was dropped on the perovskite film, and spin coating was performed at 3000 rpm for 30 s to complete the preparation of the hole transport layer Spiro-MeOTAD;
[0043] Evaporation of metal electrode layer: Place the substrate with the hole transport layer Spiro-MeOTAD on the patterned mask and fix it, then put it into the evaporation chamber of the vacuum evaporator, place silver particles on the tungsten boat, and then evacuate the evaporation chamber to a vacuum state (<10 -3 Pa) for evaporation; the evaporation rate and thickness are controlled by a film thickness meter, the rate is about 0.2nm / s, the thickness of Ag is controlled at 70nm, the evaporation of the silver electrode is completed, and a complete perovskite solar cell (PSCs device) is obtained.
[0044] Embodiment 2:
[0045] A method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell comprises the following steps:
[0046] S1: Cleaning and processing of the transparent conductive substrate, same as in Example 1;
[0047] S2: preparation of a chemical bath solution, which differs from Example 1 in that the volume fraction of the isobutanol aqueous solution is 10%;
[0048] S3: Chemical bath deposition of SnO2 electron transport layer, same as in Example 1;
[0049] S4: sequentially depositing a perovskite layer, a hole transport layer Spiro-OMeTAD and a vapor-deposited metal electrode layer on the SnO2 electron transport layer to prepare a complete perovskite solar cell. The specific method is the same as in Example 1.
[0050] Embodiment 3:
[0051] A method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell comprises the following steps:
[0052] S1: Cleaning and processing of the transparent conductive substrate, same as in Example 1;
[0053] S2: preparation of a chemical bath solution, which is different from Example 1 in that the volume fraction of the isobutanol aqueous solution is 20%;
[0054] S3: Chemical bath deposition of SnO2 electron transport layer, same as in Example 1;
[0055] S4: sequentially depositing a perovskite layer, a hole transport layer Spiro-OMeTAD and a vapor-deposited metal electrode layer on the SnO2 electron transport layer to prepare a complete perovskite solar cell. The specific method is the same as in Example 1.
[0056] Comparative Example:
[0057] A method for chemical bath deposition of an electron transport layer for a perovskite solar cell, comprising the following steps:
[0058] S1: Cleaning and processing of the transparent conductive substrate, same as in Example 1;
[0059] S2: preparation of a chemical bath solution, which differs from Example 1 in that the chemical deposition solution does not contain isobutanol;
[0060] S3: Chemical bath deposition of SnO2 electron transport layer, same as in Example 1;
[0061] A perovskite layer, a hole transport layer Spiro-OMeTAD and a vapor-deposited metal electrode layer are sequentially deposited on the SnO2 electron transport layer to prepare a complete perovskite solar cell. The specific method is the same as in Example 1.
[0062] Sample characterization and performance testing:
[0063] (1) SEM scanning was performed on the SnO2 electron transport layers prepared in Examples 1-3 and Comparative Example, and the results were as follows: Figure 1 As shown (a, b, c, and d in the figure are SEM scanning results of Examples 1-3 and the comparative example respectively), the SnO2 electron transport layer prepared in the comparative example has uneven particle size, irregular particle shape and serious aggregation phenomenon; the SEM image of the SnO2 electron transport layer of Example 1 shows relatively large particles and uneven distribution, showing a certain degree of particle aggregation phenomenon; the SnO2 electron transport layer of Example 2 has the best surface morphology, which is manifested as small and uniform particles, smooth and dense surface, regular particle shape, and less aggregation phenomenon; in Example 3, the SnO2 particles have almost no aggregation behavior, but the SnO2 particles are more dispersed, and the particles are too small, resulting in almost no SnO2 particles being observed in the SEM image.
[0064] (2) The SnO2 electron transport layers prepared in Examples 1-3 and the comparative example were tested by UV-visible light spectroscopy. The results are as follows: Figure 2 As shown, overall, the transmittance of the SnO2 electron transport layer of the comparative example is the lowest, the transmittances of Examples 1-3 are all higher than those of the comparative example, and the transmittance of Example 2 is higher than that of Examples 1 and 3, which indicates that the SnO2 electron transport layer deposited by the alcohol-assisted chemical bath of the present method effectively improves the transmittance of the SnO2 electron transport layer, among which the SnO2 electron transport layer deposited by the isobutanol chemical bath with a volume fraction of 10% in Example 2 has the best effect.
[0065] (3) The current density-voltage test was performed on the perovskite solar cells prepared in Examples 1-3 and the comparative example. The test method was as follows: first, the light intensity was calibrated using a standard silicon cell to an intensity of 100 mW·cm -2 The scanning voltage range during the test is 0V-1.2V, the data collection time interval is 100ms, and the scanning speed is 200mV / s. The test results are as follows: Figure 3-6 And as shown in Table 1.
[0066] Table 1 Photovoltaic parameters corresponding to perovskite solar cells prepared based on nO2 electron transport layers of Examples 1-3 and Comparative Example S (obtained from the corresponding current density-voltage curves)
[0067] sample Photoelectric conversion efficiency Open circuit voltage Short circuit current density Fill Factor Example 1 20.83% 1.13V <![CDATA[23.03mA / cm 2 ]]> 79.69% Example 2 22.05% 1.13V <![CDATA[24.16mA / cm 2 ]]> 80.67% Example 3 21.17% 1.13V <![CDATA[23.55mA / cm 2 ]]> 79.78% Comparative Example 20.26% 1.11V <![CDATA[22.74mA / cm 2 ]]> 80.16%
[0068] Figure 3 The current density-voltage curve of the perovskite solar cell prepared by SnO2 deposited by isobutanol chemical bath with a volume fraction of 5% in Example 1 is shown in FIG. Figure 3 As shown in Table 1, the open circuit voltage of the battery in Example 1 is 1.13 V and the short circuit current is 23.03 mA / cm 2 , the filling factor is 79.69%; Figure 4 The current density-voltage curve of the perovskite solar cell prepared by SnO2 deposited by isobutanol chemical bath with a volume fraction of 10% in Example 2 is given by Figure 4 As shown in Table 1, the open circuit voltage of the battery in Example 2 is 1.13 V and the short circuit current is 24.16 mA / cm 2 , the filling factor is 80.67%; Figure 5 The current density-voltage curve of the perovskite solar cell prepared by SnO2 deposited by isobutanol chemical bath with a volume fraction of 20% in Example 3 is shown in FIG. Figure 5 As shown in Table 1, the open circuit voltage of the battery in Example 3 is 1.13 V and the short circuit current is 23.55 mA / cm 2 , the filling factor is 79.78%; Figure 6 is the current density-voltage curve of the SnO2 perovskite solar cell deposited by the aqueous solution (without isobutyl alcohol) chemical bath in the comparative example, Figure 6 As shown in Table 1, the open circuit voltage of the comparative perovskite solar cell is 1.11 V and the short circuit current is 22.74 mA / cm 2 , the fill factor is 80.16%. The photoelectric conversion efficiency, open circuit voltage and short circuit current density of the perovskite solar cells prepared in Examples 1-3 are all higher than those in the comparative example, indicating that the electron transport layer prepared by the electron transport layer method of alcohol-assisted chemical bath deposition provided by the present invention is applied in the preparation of perovskite solar cells, which can effectively improve the open circuit voltage and short circuit current of the perovskite solar cell, thereby improving the photoelectric conversion efficiency of the perovskite solar cell.
[0069] In summary, the SnO2 electron transport layer prepared by the alcohol-assisted chemical bath deposition electron transport layer of the present method has uniform SnO2 particle distribution, reduced agglomeration, and high solar transmittance, which improves the solar light utilization rate of the perovskite solar cell, improves the open circuit voltage and short circuit current of the prepared perovskite solar cell, and improves the photoelectric conversion efficiency; in addition, the reduction of SnO2 agglomeration can improve the stability of the battery, and can also reduce the inconsistency of performance between SnO2 layers of different batches, thereby reducing the control difficulty and reducing the production cost.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for alcohol-assisted chemical bath deposition of electron transport layers for perovskite solar cells, characterized in that: The following steps are involved: S1: cleaning the conductive glass substrate to obtain a clean conductive glass substrate; S2: adding SnCl2·2H2O to an isobutyl alcohol aqueous solution to obtain a first mixed solution, adding urea to the first mixed solution to obtain a second mixed solution, and then mixing thioglycolic acid, concentrated hydrochloric acid, and the second mixed solution to complete the preparation of a chemical bath solution; S3: Soak the clean conductive glass substrate in a chemical bath solution and place it in an oven for a deposition reaction. After the reaction is completed, the conductive glass substrate is cleaned and annealed to complete the deposition of the SnO2 electron transport layer on the conductive glass substrate.
2. The method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell according to claim 1, characterized in that: In S2, the volume fraction of the isobutanol aqueous solution is 0-20%.
3. The method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell according to claim 1, characterized in that: In S2, the concentration of urea in the second mixed solution is 12-13 mg / mL.
4. The method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell according to claim 1, characterized in that: In S2, the concentration of SnCl2·2H2O in the first mixed solution is 2-3 mg / mL.
5. The method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell according to claim 1, characterized in that: In S2, the thioglycolic acid, concentrated hydrochloric acid and the mixed solution are mixed in a volume ratio of 1:50:
80.
6. The method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell according to claim 1, characterized in that: In S3, the annealing temperature is 100-200° C., and the annealing time is 1-2 hours.
7. The method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell according to claim 1, characterized in that: In S3, the temperature of the oven is 70-90°C and the time is 3-5h.
8. The method for alcohol-assisted chemical bath deposition of electron transport layers for perovskite solar cells according to claim 1, characterized in that: The conductive glass substrate is a fluorine-doped tin oxide conductive glass substrate.
9. The method for alcohol-assisted chemical bath deposition of electron transport layers for perovskite solar cells according to claim 1, characterized in that: In S1, the specific cleaning method is: ultrasonic cleaning with detergent, deionized water, anhydrous ethanol, and isopropanol for 15-30 minutes each; In S3, the specific method of cleaning is: ultrasonically cleaning the substrate with deionized water and isopropyl alcohol in sequence for 5-10 minutes.
10. A perovskite solar cell, characterized in that: The invention comprises a conductive glass substrate, an electron transport layer, a perovskite layer, a hole transport layer and an electrode layer arranged in a stacked manner, wherein the electron transport layer is an electron transport layer prepared by the method for alcohol-assisted chemical bath deposition of an electron transport layer for a perovskite solar cell according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of planar perovskite solar cell
CN109904328A
Solar cell based on quasi two-dimensional-two-dimensional perovskite and preparation method thereof
CN114824092A
Electron transport layer and preparation method and application thereof
CN115666194A
Electron transport layer and preparation method thereof, electron transport layer material, perovskite cell and preparation method thereof
CN117812975A
Stable printable formamidino perovskite ink and photovoltaic module preparation method thereof
CN118185371A
